Development and psychometric properties of a health knowledge test on six chronic conditions. Issue 12 (December 2016) - Gellert, Paul; Detel, Sibylle; Ernsting, Clemens; Oedekoven, Monika; Kuhlmey, Adelheid
Highlights: A health knowledge test on common chronic conditions was developed. General health knowledge, which based on the six specific conditions was confirmed. There is substantial relation of health knowledge with educational level. Abstract: Objectives: The aim of this study was to develop and test the psychometric properties of a health knowledge test on common chronic conditions in the general population. Methods: Operationalization based on a facet design led to 108 knowledge items on six conditions: cardiovascular disease, cancer, respiratory diseases, musculoskeletal system conditions, depression, and chronic pain. We refined the items (qualitative study 1; N = 20) and selected the items by applying a mixed Rasch model (study 2; N = 861). The psychometric properties (Study 3; N = 4144) of the remaining 24 items were tested using exploratory (split sample N = 2110) and confirmatory factor analyses (split sample N = 2034). Results: 108 items were refined within study 1, 24 of which were selected in study 2. In study 3, a general health knowledge factor was confirmed based on six subscales on specific conditions. Convergent validity was confirmed by the overlap of health knowledge with education and perceived health knowledge. Conclusion: The development and evaluation of the psychometric properties of a health knowledge test on six common conditions will improve future research on health knowledge. Practical implications: Chronic conditions present a challenge; assessing the level of health knowledge is the first step to prevent and to cope with these conditions.